The Economics of Environment and Ecology for Sustainable Development - Meeta Jakhanwal; Mukesh Kumar Mishra (ZBW - Leibniz Information Centre for Economics, 2020)
Economic growth and development are intricately linked to the sound management of environmental resources. Reducing inequalities in society and maintaining healthy ecosystems are fundamental to achieving sustainable development, yet the interactions between these goals have been largely underexplored. Ecology and economy are derived from the same root words and concerns. Economics provides important tools for understanding and managing resources. Ecological economics focuses on the value of natural services and tries to include those services into price calculations. This Paper brief focuses on how societies can create opportunities for a green and inclusive economic recovery and, aims to achieve this goal by a structured approach to valuation that helps decision-makers recognize the wide range of benefits provided by ecology and ecosystems, their values in economic terms and in decision-making. A green recovery will significantly enhance the resilience of economies and societies in the face of both the severe recession and accelerating environmental challenges. Through education, research, policy and social action, needs to transform towards an equitable and ecologically sustainable society with respect for the rights of people and nature, biological cultural diversity and to respect its ecological limits.
Keywords: Q56; Q57; Q58; 330; Ecological Economics; Environmental Economics; Sustainable Development